O Prostym Sposobie Projektowania Żelbetowymi Belek Ciągłych na Nośność Graniczna - Cohn, M.Z. (Engineering Transactions, 1963)
The work is concerned with establishing a simple rule of optimum design of reinforced beams when plastic effects are taken into account. Starting from the bending moments obtained from elastic solutions, and assuming that they reach limit values at critical sections, these values are taken as the basis of calculation. A necessary reduction of limit moments due to factored live loads is next proposed. A so-called “serviceability criterion" is used for this purpose. According to this criterion, the yield safety parameters for all possible elementary mechanism should be equal. The optimal design of a five-span, continuum beam under uniform load was considered in order to illustrate the above method.